Experiences of India's community health workers and women during the COVID-19 pandemic. - Jalali, Falak; Nichols, Carly; Fischer, Harry (Swedish University of Agricultural Sciences, 2023)
The data comprises open ended interviews conducted with rural health care workers (known as ASHAs) and women in the Sirmaur District of Himachal Pradesh, India. The data documents ASHAs' experiences acting as frontline healthcare workers during the COVID-19 pandemic, including their perceptions of risks, challenges, and professional responsibilities. The data also documents rural women's experiences of managing their households, caring for children, and navigating the challenges that they faced during this highly uncertain time. Respondents were identified through snowball sampling, and all interviews were conducted through telephone conversations due to pandemic-related travel restrictions.

Methods and questionnaires
Our data collection was guided by two sets of questions:
- The “General” Covid-19 questionnaire includes questions about household labor roles, livelihoods, care for children, and emotional experiences navigating the COVID-19 Pandemic.
- The “Community health worker” (ASHA) questionnaire includes questions for community health care workers, their roles and responsibilities, and experiences as frontline healthcare workers during the COVID-19 pandemic.

Interviews:
All interviews were conducted over the phone due to pandemic-related travel restrictions. The questionnaires identified main topics for discussion, however the interviews were semi-structured. We allowed the respondent to share their thoughts and experiences of their own choosing and to direct the conversation where they wanted to take it. We conducted additional follow-up interviews where the respondents agreed to do so.

Sampling:
Respondents were contacted through snowball sampling. Initial contacts were made through an NGO in the Sirmaur District as well as through field staff employed on the research project, "Institutional Networks and Self-Organized Adaptation". After making initial contact with several respondents, they were able to suggest others to speak with from the area. The sample is thus non-random. We spoke with whomever we were able to get in contact with and who was willing to spend time speaking with us over the phone.

Datasetet består av intervjuer med vårdpersonal (s.k. ASHAs) och kvinnor på landsbygden i Sirmaurdistriktet i Himachal Pradesh, Indien. Intervjuerna dokumenterar ASHA-arbetarnas upplevelser under COVID-19-pandemin, bland annat deras upplevelser av risk, utmaningar och ansvar under pandemin. Intervjuerna med kvinnor på landsbygden i samma region beskriver deras upplevelser av att hantera hushåll, barn och andra utmaningar under pandemin. Respondenterna valdes genom snöbollsmetoden och intervjuerna utfördes över telefon p.g.a. pandemirelaterade reserestriktioner. Se den engelska beskrivningen för mer detaljer.
Experiences of India's community health workers and women during the COVID-19 pandemic.
Keywords: COMMUNITY HEALTH SERVICES; DISTRIKTSVÅRD; RURAL DEVELOPMENT; LANDSBYGDSUTVECKLING; covid-19; covid-19; ASHAs; ASHAs; health governance; health governance; women's labor; women's labor; Health care services and policies; Hälso- och sjukvårdstjänster och -politik; General health and well-being; Allmän hälsa och välbefinnande; Gender and gender roles; Kön och könsroller; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Human Geography; Kulturgeografi; Work Sciences; Arbetslivsstudier; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin